(3GdWQjb Gdi EMJQGa GdHQeLI HESJYeGd (BORACLE /s - (3YRH, YRH eMeOs ((3GdbGgQI(B: s (3OGQ GdcJH GdYdejI ddfTQ hGdJhRjY(B, s, 2003)
(3GdCYOGO GdeWdhHI ddYed eY (BORACLE -(3ebOeI Yf bhGYO GdHjGfGJ hYfGUQ bGYOI GdHjGfGJ (BORACLE- (3EfTGA YfGUQ bGYOI GdHjGfGJ(B- (3ebOeI ddZI GdHQeLI(B- (3GdOhGd hGdHQGeL GdaQYjI(B- (3ebOeI Yf eWhQ GdHQGeL(B- (3eUee GdfeGPL(B- (3JTZjd ChGeQ GdfeGPL(B- (3bhGFe GdENJjGQGJ(B- (3eUee GdJbGQjQ(B- (3JMSjf Tcd GdJbQjQ(B- (3OQGSI hJMdjd hJUeje hEYOGO JWHjb HSjW hJWHjb eJcGed(B- (3HQeLI GdfeGPL GdeJbOeI(B.s
Keywords: (3GdHQeLI(B- (3GdMGSHGJ GdEdcJQhfjIs; (3GdHQeLjGJs; (3GdMGShHs; (3dZGJ GdHQeLI(B- (3ChQGcds